Reconstitution of regulatory properties of adenylate cyclase in Escherichia coli extracts. - Reddy, P (1985)
The inhibition of adenylate cyclase activity of Escherichia coli by methyl alpha-glucoside has been demonstrated in intact or in permeable cells but not in cell-free extracts. In intact or permeable cells, this inhibition is demonstrable only in strains expressing the genes for proteins of the phosphoenolpyruvate:glycose phosphotransferase system (PTS); in permeable cells, the inhibition also requires potassium phosphate. Using homogeneous proteins of the PTS, we have reconstituted in cell-free extracts many of the features of the regulated form of adenylate cyclase: (i) In the absence of K2HPO4, permeable cells have lower adenylate cyclase activity than extracts; addition of homogeneous PTS proteins to the extracts brings adenylate cyclase activity close to the level observed in permeable cells. (ii) The low activity observed in permeable cells is stimulated by potassium phosphate; this stimulation is also observed in extracts supplemented with PTS proteins and phosphoenolpyruvate. (iii) In permeable cells, potassium phosphate-stimulated adenylate cyclase activity is inhibited by methyl alpha-glucoside or pyruvate; extracts behaved similarly when supplemented with PTS proteins, K2HPO4, and phosphoenolpyruvate. Thus, the regulated form of adenylate cyclase has been reconstituted in cell-free extracts by addition of homogeneous PTS proteins.